Analisis Overall Equipment Effectiveness (OEE) pada Mesin Caterpillar Type 3512B - Khoirul Hafiz; Erwin Martianis (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
PT. PLN (Persero) ULPLTD Bagan Besar PLTD Bengkalis where the diesel engine is the prime mover. In this case, the role of engine maintenance is needed so that there are no obstacles in the process of distributing community power, especially for Bengkalis Island. Therefore, it is necessary to identify to measure the level of effectiveness of the work of the machine by using the Overall Equipment Effectiveness (OEE) method. Overall Equipment Effectiveness (OEE) is a method of measuring the overall effectiveness of a production machine that involves measuring the level of effectiveness of time, the level of machine performance, and the level of quality of products produced. Measuring the level of work effectiveness of the Caterpillar Type 3512B engine with the Overall Equipment Effectiveness (OEE) method at PT. PLN (Persero) ULPLTD Bagan Besar PLTD Bengkalis in the December 2018 - March 2019 period the results obtained do not meet the value of the Word Class Ideal OEE with a percentage value below 85%.